Kinetics of Calcium Accumulation in Acute Myocardial Ischemic Injury - Shen, Anthony C. (1972)
The effect of ischemic injury on calcium uptake by dog myocardial cells was investigated in tissue damaged by transient or permanent occlusion of the circumflex branch of the left coronary artery. Tracer doses of (45)CaCl(2) were given at selected intervals before or after occlusion, and tissue uptake was measured in damaged and control left ventricular myocardium. No significant uptake of (45)Ca occurred after 60 minutes of ischemia produced by permanent occlusion of a coronary artery. However, 40 minutes of ischemia followed by 10 minutes of arterial reflow resulted in an 18-fold increase in Ca uptake in the injured tissue. Tissue (45)Ca increased linearly up through 10 minutes of arterial reflow but did not increase further with an additional 10 minutes of reflow. Myocardium reversibly injured by 10 minutes of ischemia followed by 20 minutes of arterial reflow did not accumulate excess (45)Ca. Calcium uptake is assumed to be an active process associated with mitochondrial accumulation of calcium into dense intramitochondrial granules of calcium phosphate. The uptake is a feature of irreversible cellular injury, but occurs only when arterial blood flow is present. The mechanism of the uptake has not been established. It appears to be related to defects in cellular permeability or mitochondrial function.